2014
DOI: 10.1128/aem.01012-14
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Pathogenic Oomycetes, Escherichia coli Strains, and Salmonella spp. Frequently Found in Surface Water Used for Irrigation of Fruit and Vegetable Crops in New York State

Abstract: bIn the United States, surface water is commonly used to irrigate a variety of produce crops and can harbor pathogens responsible for food-borne illnesses and plant diseases. Understanding when pathogens infest water sources is valuable information for produce growers to improve the food safety and production of these crops. In this study, prevalence data along with regression tree analyses were used to correlate water quality parameters (pH, temperature, turbidity), irrigation site properties (source, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 33 publications
5
22
0
Order By: Relevance
“…This is supported by the fact that the diversity of ATs in soil samples collected after irrigation events was not statistically different from the diversity of ATs in water samples collected from Fall Creek, the source of irrigation water used in this study. These findings are consistent with findings of previous studies (14,25,26,47,51,52) that identified irrigation water as a potential preharvest source of bacterial contamination of produce. Multiple studies have also reported significant associations between irrigation water and fresh produce contamination (12,13,19,20).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is supported by the fact that the diversity of ATs in soil samples collected after irrigation events was not statistically different from the diversity of ATs in water samples collected from Fall Creek, the source of irrigation water used in this study. These findings are consistent with findings of previous studies (14,25,26,47,51,52) that identified irrigation water as a potential preharvest source of bacterial contamination of produce. Multiple studies have also reported significant associations between irrigation water and fresh produce contamination (12,13,19,20).…”
Section: Discussionsupporting
confidence: 93%
“…The relationship between irrigation and L. monocytogenes isolation in this study may be explained by the fact that surface water is a known reservoir of foodborne pathogens in produce production environments (22,(52)(53)(54)(55)(56). As our study and other studies (14,21,25,47,51,52) have demonstrated, irrigation is an important risk factor for preharvest produce contamination, particularly if the irrigation water is drawn from a surface water source. Therefore, intervention at the irrigation level may decrease the risk of L. monocytogenes contamination of produce.…”
Section: Discussionsupporting
confidence: 54%
“…Use of poultry litter which has been heat treated and pelletized (heat-treated poultry pellets [HTPP]) as a BSAAO may provide sufficient nutrients to leafy green vegetables while minimizing the risk of enteric bacterial contamination associated with untreated manure in the preharvest environment. However, introduction of pathogens through the use of contaminated irrigation water (14,15), scat from wild animals (16), bird droppings (17,18), and runoff from nearby livestock operations (19)(20)(21) are all potential routes that may introduce bacterial pathogens to soils in crop fields, and the presence of HTPP in soil may aid survival, as evidenced by increased growth in soil extracts prepared with HTPP-amended soil (22).…”
mentioning
confidence: 99%
“…Recent investigations have focused on irrigation water as a potential environmental source of Salmonella for preharvest contamination of produce (8)(9)(10)(11)12). Furthermore, the static nature of some irrigation ponds may sustain persistent populations of Salmonella (13,14).…”
mentioning
confidence: 99%